2020
DOI: 10.11134/btp.2.2020.8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Conditions for The Multiplex PCR for Diagnostics of Horse Strangles with Subspecies Differentiation of Streptococcus Equi Subsp Equi

Abstract: As a result of the work performed, the conditions for setting up multiplex PCR with electrophoretic detection for the diagnosis of horse strangles were determined, allowing the identification and differentiation of S. equi subsp. equi in one reaction. It was found that the developed PCR protocol for the detection and species differentiation of S. equi subsp. equi with electrophoretic detection in a “multiplex” format has a high specificity and does not lead to amplification of PCR products with DNA of closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Subsequently, abscesses are formed on the submandibular lymph nodes and will develop to become firm and painful, which can cause tightening in the equine’s esophagus; hence, the term Strangles. These abscesses rupture a week to 10 days post onset of clinical signs but can take up to 4 weeks in some cases [ 85 , 86 , 87 ], with uncomplicated cases recovering at about 1–2 weeks post rupture [ 78 ]. Severe complications can occur, including guttural pouch empyema, purpura haemorrhagica, myositis, internal abscessation and further spread of the bacteria internally [ 79 , 85 , 88 ].…”
Section: Equine Bacterial Diseases Of Biosecurity Relevancementioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, abscesses are formed on the submandibular lymph nodes and will develop to become firm and painful, which can cause tightening in the equine’s esophagus; hence, the term Strangles. These abscesses rupture a week to 10 days post onset of clinical signs but can take up to 4 weeks in some cases [ 85 , 86 , 87 ], with uncomplicated cases recovering at about 1–2 weeks post rupture [ 78 ]. Severe complications can occur, including guttural pouch empyema, purpura haemorrhagica, myositis, internal abscessation and further spread of the bacteria internally [ 79 , 85 , 88 ].…”
Section: Equine Bacterial Diseases Of Biosecurity Relevancementioning
confidence: 99%
“…Culturing was originally used for detection, but multiple studies reported the inadequacy of this method due to the variability of clinical sensitivity [ 45 , 96 ], which will be discussed further below. Treatment and prognosis are conditional to the stage of the disease; however, most horses will fully recovery with minimal supportive care [ 79 , 86 ]. As with R. equi infections, antibiotic use is debated amongst scientists [ 86 , 98 ].…”
Section: Equine Bacterial Diseases Of Biosecurity Relevancementioning
confidence: 99%
See 2 more Smart Citations